Taxonomic clarification of Silene dawoensis (Caryophyllaceae): synonymization with S. batangensis and reinstatement of S. longiuscula - Feng Yang; Huan-Chong Wang (PhytoKeys)
Based on a comprehensive analysis of type materials, protologues, herbarium specimens, and field observations, this study clarifies the taxonomic status of Silene dawoensis and related species in China. Our findings reveal that S. dawoensis shares key similarities with S. batangensis, including leaf shape, inflorescence type, and calyx structure, and therefore we have placed S. dawoensis as a synonym of S. batangensis. Additionally, specimens historically misidentified as S. dawoensis are reassigned to S. markamensis, a species previously overlooked in regional floras. Concurrently, based on diagnostic differences in leaf shape, calyx length, and petal morphology, we reinstate S. longiuscula as a distinct species, previously treated as a synonym of S. dawoensis. Typification for S. batangensis and S. dawoensis is given. Descriptions, distribution maps, taxonomic notes, and morphological comparison table are provided for these three species.